Association between Sick Building Syndrome and Indoor Environmental Quality in Slovenian Hospitals: A Cross-Sectional Study - Kalender Smajlović, Sedina (Int J Environ Res Public Health, 2019)
Increased exposure times to various health risk factors and the vulnerability of building users might result in significantly higher prevalence rates of sick building syndrome (SBS) in a hospital setting compared to other indoor environments. The purpose of our study was to assess the association between SBS symptoms and measured environmental parameters at a Slovenian general hospital. A combination of a self-assessment study and field measurements was conducted in order to estimate the health risk factors for SBS symptoms among the users of a Slovenian general hospital. The Chi-square test was used to analyse the association between observed health and environmental parameters. The response rate was 67.5%. A total of 12.0% of healthcare workers at hospital wards reported at least six SBS symptoms, 19.0% reported 2–3 SBS symptoms. At the observed hospital wards, the most deviations were recorded for the level of lighting (83.3%), noise level (73.6%), and room temperature (55.3%). A statistically significant association was found between indoor environmental quality and skin-related SBS symptoms (χ(2) = 0.009; p = 0.006). This information will be of great value in defining an integral strategy of environmental health activities aimed at healthier indoor environmental quality in hospitals.